A pragma- semantic model for ideology identification in political media discourse: an interdisciplinary methodology for the socio- cognitive approach - Khalil, Huda H. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The paper is a critical discourse analysis of political discourse. It relies on van Dijk’s socio- cognitive approach which employs miscellaneous linguistic methodologies as input to support the interdisciplinarity of the socio-cognitive base. The paper adopts an eclectic model that combines pragmatic and semantic concepts as a methodology for the socio- cognitive approach. The pragma- semantic interface has always produced better holistic, integrated, and objective linguistic inference. The eclectic model combines Sabet & Zhang’s (2015) pragmatic functions of vague expressions (on the pragmatic level) and the semantic macrostructures and the semantic microstructures (on the semantic level). Wodak (2007) emphasises the vitality of the pragmatics in any critical discussion that analyses indirect and inferred linguistic techniques and biased utterances in order to identify and evaluate political discourse. Since vague expressions overlap sometimes in performing pragmatic functions, the pragmatic component of the eclectic model is further supported by the semantic concepts of semantic macrostructure and semantic microstructure. The data is collected from the White House Press Releases (issued in 2014 when ISIS took hold of major Iraqi cities) on Iraq. Such discourse is globally interesting and can shape public opinion about the critical events and realities in Iraq at that time. The analysis has proved the workability of the pragmatic- semantic integration and the paper has come up with a set of concluding remarks.